2021
DOI: 10.31849/jip.v17i2.5191
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan tumpukan beras Bulog terhadap populasi kutu beras (Sitophilus oryzae L.) dan mutu beras selama masa simpan di Kabupaten Jayawijaya

Abstract: This study was aimed to find out the effect of rice pile on pest population and the quality of rice during storage; find out which pile of Bulog rice produces the populations of Rice Weevil pest the most during storage; find out which pile of Bulog rice that produces the best quality during storage. This research was conducted in the laboratory of STIPER Petra Baliem Wamena and the Faculty of Agricultural, Universitas Gadjah Mada Yogyakarta. The observation was done in 1 year, from March 2019 to March 2020. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…A. H., Harun, N. Y., Bilad, M. R., Afzal, M. T., Parvez, A. M., Roslan, F. A. S., Rahim, S. A., Vinayagam, V. D., & Afolabi, H. K. 2021; Utami & Ulfa, 2022). If the water content of unhulled rice is lower than 14%, the rice grains will easy to break (Mahanani & Inrianti, 2021;Yang, W., Zheng, Y., Sun, W., Chen, S., Liu, D., Zhang, H., Fang, H., Tian, J., & Ye, X., 2020), so rice produced is more in the form of broken rice grains. Meanwhile, if the water content of unhulled rice exceeds 14%, the grinder machine will work very hard, and the resulting bran will clog the sieve holes during grinding, so the rice produced is easily cracked and broken (Kumoro, A. C., Lukiwati, D. R., Praseptiangga, D., Djaeni, M., Ratnawati, R., Hidayat, J. P., & Utari, F. D., 2019; Permatasari, 2020; Tang, Z., Li, Y., Zhang, B., Wang, M., & Li, Y., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…A. H., Harun, N. Y., Bilad, M. R., Afzal, M. T., Parvez, A. M., Roslan, F. A. S., Rahim, S. A., Vinayagam, V. D., & Afolabi, H. K. 2021; Utami & Ulfa, 2022). If the water content of unhulled rice is lower than 14%, the rice grains will easy to break (Mahanani & Inrianti, 2021;Yang, W., Zheng, Y., Sun, W., Chen, S., Liu, D., Zhang, H., Fang, H., Tian, J., & Ye, X., 2020), so rice produced is more in the form of broken rice grains. Meanwhile, if the water content of unhulled rice exceeds 14%, the grinder machine will work very hard, and the resulting bran will clog the sieve holes during grinding, so the rice produced is easily cracked and broken (Kumoro, A. C., Lukiwati, D. R., Praseptiangga, D., Djaeni, M., Ratnawati, R., Hidayat, J. P., & Utari, F. D., 2019; Permatasari, 2020; Tang, Z., Li, Y., Zhang, B., Wang, M., & Li, Y., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the calcium propionate did not have any capability to protect rice bran from insect attack. According to Mahanani and Inrianti (2021), the population of beetles increased due to storage time dan relative humidity. Pratiwi and Ananda (2021) reported that at a temperature of 20-30 o C and relative humidity of 60-70% the insect (C. ferrugineus) was found grow well and at a temperature of 40 o C and relative humidity of 35% was suppressed and more mortality.…”
Section: Number Of Beetlesmentioning
confidence: 99%
“…Pendapat tersebut sesuai dengan pernyataan Hendrival dan Melinda (2017), bahwa kepadatan populasi S. oryzae yang diinfestasikan semakin tinggi dapat menyebabkan semakin tinggi pula persentase kehilangan bobot dan persentase kerusakan beras berlubang akibat serangan S. oryzae. Jumlah populasi hama berkorelasi positif dengan hasil akhir bobot beras, populasi S. oryzae semakin banyak menyebabkan hasil akhir bobot beras menurun (Mahanani dan Inrianti, 2021;Rizal dkk., 2019). KESIMPULAN 1.…”
Section: Dhakshinamoorthyunclassified